Depression and Abuse During Medical Internshipsin Peruvian Hospitals - Vilchez Cornejo, Jennifer (2018)
Objective: To estimate the prevalence of depression and abuse and identify the associatedfactors in medical interns in Peruvian hospitals.Methods: We conducted a multicentre, cross-sectional and analytical study during themonths of March to May 2016. We included medical interns from 18 Peruvian hospitals,in Lima and provinces. We used a survey that included sociodemographic data and a scaleto measure the perception of abuse (psychological, physical and sexual). In addition, weused the Spanish version of the PHQ-9 to evaluate depression. We used Poisson regressionwith robust variances to calculate prevalence ratios (PRs).Results: A total of 402 medical interns participated in the study, the median age was 25[IQR: 21–33], and 52.7% were male. Moreover, 25.4% of them suffered from depression. In theadjusted model, the variables associated with depression were age (PRa = 1.15), the numberof hours they sleep per day (PRa = 1.23), being a woman (PRa = 3.33), performing the intern-ship in a province (PRa = 0.25), studying at a public university (PRa = 0.64), living with parents(PRa = 0.65) or alone (PRa = 0.33), and having perceived some type of abuse (PRa = 1.07).Conclusions: A quarter of surveyed medical interns had depression. Early screening is neces-sary to identify perceived abuse and other triggering depression factors that may adverselyaffect work performance and overall mental health during medical internships.